2010
DOI: 10.1095/biolreprod.110.083931
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Expression of the Rat Myometrial Relaxin Receptor (RXFP1) in Late Pregnancy Is Partially Mediated by the Presence of the Conceptus1

Abstract: The actions of relaxin are mediated by relaxin family peptide receptor 1 (Rxfp1). In pregnant mice, myometrial Rxfp1 expression decreases at term, coinciding with the highest level of circulating relaxin. This down-regulation in Rxfp1 in reproductive tissues has not been investigated in other pregnant animals, nor are the regulatory mechanisms known. In the present study, we examined Rxfp1 gene and protein expression in the nonpregnant, pregnant, and postpartum rat uterus. The potential effects of local concep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
20
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 43 publications
4
20
0
Order By: Relevance
“…In rats, RXFP1 was expressed in the myometrium from early to mid-gestation at levels similar to those determined in nonpregnant rat myometrium, followed by a significant reduction during late gestation. This downregulation in myometrial RXFP1 expression at the end of gestation is indicative of a functional withdrawal of relaxin and may represent a novel mechanism for the activation of spontaneous uterine contractions at labor (Vodstrcil et al 2010). As our study did not include late pregnancy, decreasing levels of RXFP1 could not be shown for cats.…”
Section: Discussionmentioning
confidence: 80%
“…In rats, RXFP1 was expressed in the myometrium from early to mid-gestation at levels similar to those determined in nonpregnant rat myometrium, followed by a significant reduction during late gestation. This downregulation in myometrial RXFP1 expression at the end of gestation is indicative of a functional withdrawal of relaxin and may represent a novel mechanism for the activation of spontaneous uterine contractions at labor (Vodstrcil et al 2010). As our study did not include late pregnancy, decreasing levels of RXFP1 could not be shown for cats.…”
Section: Discussionmentioning
confidence: 80%
“…These actions of relaxin are now known to be mediated through a leucine-rich repeat containing heterotrimeric guanine nucleotide-binding, G protein-coupled receptor, known as relaxin family peptide receptor 1 (RXFP1). We demonstrated significant decreases in myometrial Rxfp1 gene and protein expression in late gestation and during spontaneous labor in the rat and proposed that the RXFP1 receptor down-regulation is a mechanism of functional relaxin withdrawal necessary for the activation of CAPs in the myometrium [6].…”
Section: Introductionmentioning
confidence: 85%
“…Plasma was collected, frozen, and stored at À808C for steroid assay. The uteri were removed immediately after the animal was killed, and the decidualized endometrium and fetal-placental units were removed from the uterine wall as described previously [6]. The myometrium was then snap-frozen in liquid nitrogen and stored at À808C until RNA extraction.…”
Section: Experimental Designmentioning
confidence: 99%
See 2 more Smart Citations